Biocompatible Polymer Embedded In Light-Sensitive Materials: Investigation Of Structural Properties - Mei, Gan Siew; A. R., Yuvaraj; Siti Maznah, Kabeb; M. M., Yusoff; V. G., Chigrinov; Hegde, Gurumurthy (Universiti Malaysia Pahang, 2014)
Cost effective biocompatible polymer embedded in light-sensitive materials is reported for use in the photonics industry. Adhesion of photosensitive materials is improved by mixing them with highly viscous biocompatible substances. HEC (hydroxyethyl cellulose) is used as a biocompatible substance to study the photoalignment of light sensitive material SD-1. The mixture provides excellent results with good adhesion, better photoalignment quality and is highly suitable for plastic displays.